Pengaruh Sense of Humor dan Family Support terhadap Academic Burnout pada Mahasiswa di Universitas Negeri Padang - Wiby, Alifeannisa Putri; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2024)
This study aims to examine the effect of sense of humor and family support on academic burnout in students at Padang State University. This study also examines the effect of each independent variable (sense of humor and family support) on the dependent variable (academic burnout). The sample consisted of 340 students at Padang State University taken using the snowball sampling technique. This study used a measuring instrument for academic burnout using the Maslach Burnout Inventory - Student Survey (MBI-SS), a measuring instrument for family support using The Multidimensional Scale of Perceived Social Support (MSPSS), and a measuring instrument for sense of humor using the Multidimensional Sense of Humor Scale (MSHS). The testing conducted in this study with multiple linear analysis using SPSS Statistic 20.0 for Windows software. The results showed that there was a positive and significant effect of sense of humor and family support on academic burnout.